Effects of Implementing Efficiency Techniques in the Plastics Industry in Germany and Western Australia – A Comparative Modelling Assessment - Schlüter, Alexander; Rosano, Michele; Böhm, Stefan; Calisir, Necat; Hesselbach, Jens

Energieströme simulieren: Vom Prozess bis zur Fabrik - Schlüter, Alexander; Martin, Lars; Schäfer, Mirko (Energie- und klimaeffiziente Produktion: Grundlagen, Leitlinien und Praxisbeispiele)

Von der Modellbildung zur Simulation: Die Vorgehensweise - Schlüter, Alexander; Schäfer, Mirko (Energie- und klimaeffiziente Produktion: Grundlagen, Leitlinien und Praxisbeispiele)

Prozesswärme und Abwärmenutzung - Schlüter, Alexander; Leischner, Frank; Rommel, Benjamin (Energie- und klimaeffiziente Produktion: Grundlagen, Leitlinien und Praxisbeispiele)

Effects of Implementing Efficiency Techniques in the Plastics Industry in Germany and Western Australia – A Comparative Modelling Assessment, talk - Schlüter, Alexander; Rosano, Michele; Böhm, Stefan; Calisir, Necat; Hesselbach, Jens

Wenn aus Wärme Kälte wird. Interview - Schlüter, Alexander

Potenziale erkennen und fördern. Qualität entwickeln. Band 2: Anregungen zur Gestaltung der Potenzialanalyse - Lippegaus, Petra; Voigt, Birgit

Potenziale erkennen und fördern. Qualität entwickeln. Band 1: Potenzialanalyse in Theorie und Praxis - Lippegaus, Petra; Voigt, Birgit

Kompetenzfeststellung, Potenzialanalyse – viel Wind und nichts dahinter? - Lippegaus, Petra (Kompetenzen feststellen)

Aktuelle Entwicklungen in der „Benachteiligtenförderung" - Lippegaus, Petra (Theorie und Praxis der sozialen Arbeit Heft 1/2012)

Dual loops meshing - Campen, Marcel; Bommes, David; Kobbelt, Leif (ACM Transactions on Graphics)
We present a theoretical framework and practical method for the automatic construction of simple, all-quadrilateral patch layouts on manifold surfaces. The resulting layouts are coarse, surface-embedded cell complexes well adapted to the geometric structure, hence they are ideally suited as domains and base complexes for surface parameterization, spline fitting, or subdivision surfaces and can be used to generate quad meshes with a high-level patch structure that are advantageous in many application scenarios. Our approach is based on the careful construction of the layout graph's combinatorial dual. In contrast to the primal this dual perspective provides direct control over the globally interdependent structural constraints inherent to quad layouts. The dual layout is built from curvature-guided, crossing loops on the surface. A novel method to construct these efficiently in a geometry- and structure-aware manner constitutes the core of our approach.

A Practical Guide to Polygon Mesh Repairing - Campen, Marcel; Attene, Marco; Kobbelt, Leif (Eurographics 2012 Tutorials)
Digital 3D models are key components in many industrial and scientific sectors. In numerous domains polygonmeshes have become a de facto standard for model representation. In practice meshes often have a number ofdefects and flaws that make them incompatible with quality requirements of specific applications. Hence, repairingsuch defects in order to achieve compatibility is a highly important task - in academic as well as industrial applications. In this tutorial we first systematically analyze typical application contexts together with their requirementsand issues, as well as the various types of defects that typically play a role. Subsequently, we considerexisting techniques to process, repair, and improve the structure, geometry, and topology of imperfect meshes,aiming at making them appropriate to case-by-case requirements. We present seminal works and key algorithms,discuss extensions and improvements, and analyze the respective advantages and disadvantages depending onthe application context. Furthermore, we outline directions where further research is particularly important orpromising.

Variational Tangent Plane Intersection for Planar Polygonal Meshing - Zimmer, Henrik; Campen, Marcel; Herkrath, Ralf; Kobbelt, Leif (Advances in Architectural Geometry, AAG 2012, Paris, France, September 27-28, 2012)

Rationalization of Triangle‐Based Point‐Folding Structures - Zimmer, Henrik; Campen, Marcel; Bommes, David; Kobbelt, Leif (Computer Graphics Forum)
Abstract In mechanical engineering and architecture, structural elements with low material consumption and high load‐bearing capabilities are essential for light‐weight and even self‐supporting constructions. This paper deals with so called point‐folding elements – non‐planar, pyramidal panels, usually formed from thin metal sheets, which exploit the increased structural capabilities emerging from folds or creases. Given a triangulated free‐form surface, a corresponding point‐folding structure is a collection of pyramidal elements basing on the triangles. User‐specified or material‐induced geometric constraints often imply that each individual folding element has a different shape, leading to immense fabrication costs. We present a rationalization method for such structures which respects the prescribed aesthetic and production constraints and finds a minimal set of molds for the production process, leading to drastically reduced costs. For each base triangle we compute and parametrize the range of feasible folding elements that satisfy the given constraints within the allowed tolerances. Then we pose the rationalization task as a geometric intersection problem, which we solve so as to maximize the re‐use of mold dies. Major challenges arise from the high precision requirements and the non‐trivial parametrization of the search space. We evaluate our method on a number of practical examples where we achieve rationalization gains of more than 90%.

An evaluation of measures to dissociate language and communication disorders from healthy controls using machine learning techniques - Gaspers, J; Thiele, K; Cimiano, P; Foltz, A; Stenneken, P; Tscherepanow, M (IHI '12: Proceedings of the 2nd ACM SIGHIT International Health Informatics Symposium)

Paracyclophane Derivatives in Frustrated Lewis Pair Chemistry - Greb, Lutz; Paradies, Jan (Topics in Current Chemistry)

Soziale Dimensionen visueller Kommunikation in hoch- und spätmittelalterlichen Frauenkommunitäten – Stifte, Chorfrauenstifte und Klöster im Vergleich - Mersch, Katharina Ulrike

Innovationen auf der Grundlage von Traditionen: Kanonikerreform, Selbstreflexivität und Konventsgeschichte im Miniaturenprogramm des Hohenburger Hortus Deliciarum - Mersch, Katharina Ulrike (Innovation in Klöstern und Orden des Hohen Mittelalters. Aspekte und Pragmatik eines Begriffs)

Miller, Sarah Alison, Medieval Monstrosity and the Female Body. (Routledge Studies in Medieval Religion and Culture, Vol. 8.) London/New York, Routledge 2010 - Mersch, Katharina Ulrike (Historische Zeitschrift)

Naturalistic arm movements during obstacle avoidance in 3D and the identification of movement primitives - Grimme, Britta; Lipinski, John; Schöner, Gregor (Experimental brain research)